Bioactivity of essential oils of zingiber officinalis and achyranthes aspera against mosquitoes - Khandagle, Abhay J.; Tare, Vrushali S.; Raut, Kishor D.; Morey, Rashmi A. (Parasitology Research, 2011)
Due to the global health problems associated with mosquito-borne diseases, over two million people primarily in the tropical countries are at risk. The widely and commonly used chemical method though effective, has some major disadvantages making insect control practically difficult. In view of the above, it is unavoidable to search for new molecules, which are eco-friendly, cheaper, and safer. The present study deals with evaluation of bioactive potential of two commonly occurring plants against mosquitoes presenting an alternative to the conventional chemical methods. Essential oils extracted by steam distillation from rhizome of Zingiber officinalis and leaf and stem of Achyranthes aspera were evaluated for larvicidal, attractant/repellent, and oviposition attractant/deterrent activity against two mosquito species viz. Aedes aegypti and Culex quinquefasciatus. The highest larvicidal activity, i.e., LC(50) = 154 ppm and LC(50) = 197 ppm for A. aegypti and C. quinquefasciatus, respectively was shown by Z. officinalis. This oil also offers 5-h protection at the concentration of 0.5 mg/cmA(2) from both mosquito species. The highest oviposition deterrence activity was exhibited by A. aspera stem oil, i.e., 100% and 85.71%, in case of A. aegypti and C. quinquefasciatus, respectively, at the concentration of 0.1%. These results reveal that both these oils have control potential against A. aegypti and C. quinquefasciatus.